Prevalence and factors associated with comorbidities in Iranian patients with type 2 diabetes: A national study - Koushan Hajiuni; Sarmad Salehi; Zahra Rajabli; Sina Azadnajafabad; Samaneh Akbarpour; Samaneh Asgari; Nazila Rezaei (PLoS ONE, 2026)
Introduction Type 2 diabetes (T2DM) is often accompanied by comorbidities such as hypertension (HTN), cardiovascular disease (CVD), and chronic kidney disease (CKD), which increase the disease burden and complicate its management. In Iran, where diabetes prevalence is growing, understanding the extent and determinants of these comorbidities is crucial for improving clinical care and informing national public health strategies. Materials and methods We used data from the WHO STEPwise approach to non-communicable diseases risk factor surveillance (STEPS) 2021 to assess the prevalence of comorbidities among Iranian patients with T2DM. Comorbidity was defined as ≥ 2 of: HTN, CKD, history of CVD, or cancer. Multivariable logistic regression was done to identify the potential socio-demographic factors associated with comorbidities. Results Of a total of 2,900 participants aged 25-70 years with T2DM (56.24% women), 27.00% (95% confidence interval (CI): 24.74–29.40) had no comorbidity, 39.82% (95% CI: 37.26–42.43) had one comorbidity (HTN: 79.62%, CKD: 10.66%, CVD: 8.64%, cancer: 1.09%), and 33.18% (95% CI: 30.58–35.89) had ≥ 2 comorbidities. The prevalence of comorbidity was significantly associated with male gender, age ≥ 60 years, living in a rural area, body mass index >30 kg/m2 (all p-values < 0.05). However, higher years of schooling, being employed, and physical activity ≥ 150 min/week were associated with lower odds of comorbidities. Discussion Over 70% of Iranian adults have additional health conditions alongside diabetes, which significantly impact public health and underscore the need for personalized and multi-faceted preventive approaches.